Academic researchers, come on! Integrate social media in pedagogy - Sharma, Vipin Kumar; Begum, Suraj (Institute of Advanced Engineering and Science, 2024)
Teaching and learning have changed tremendously from traditional teaching to teaching integrating social media (SM) because of immense educational technological advancements and pedagogical innovation. Teachers, thus far, use conventional teaching as a seasoning tool and meet adaptability issues to the new learning environment. In this paper, we define SM, its related aspects, the vitality of social media networks (SMN), and how SM facilitates teaching and learning in tertiary education. It also contends with the benefits of their integration into pedagogy by teachers and students and answers a few fundamental questions on integrating SMN in teaching and learning. Accordingly, a few challenges do appear at different stages that scare us to reflect on SM as a distractor to pedagogy. To integrate and identify challenges in learning and teaching, we claim that a curriculum should be designed incorporating SMN as catalysts and managed as a learning community. The resources needed to operate SMN are also illustrated for both stakeholders to utilize and work together to collaborate for the learner-centered approach to teaching where learners use SMN to share, discuss course materials, post their assignments, get feedback, and interact beyond time, place, and location without any restrictions.